Implementasi Metode TOPSIS Untuk Pemilihan Konten Berkualitas Pada Konten Edukasi Berdasarkan Multi Kriteria - Qasos, Lailil; b, bustami; Agusniar, Cut (E-Jurnal Universitas Samudra, 2025)
The rapid development of digital technology has increased the production of educational content on social media platforms, including TikTok. However, the abundance of available content makes it difficult for content creators to select high-quality references. Therefore, this study develops a decision support system using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to evaluate and rank the best educational videos. This study utilizes 200 educational videos from TikTok, assessed based on seven criteria, namely Hook, visual quality, audio quality, content relevance, text narration, duration, and the number of Likes. Each video is weighted based on expert interviews and analyzed using the TOPSIS method to generate the best content rankings. The results show that the video with the highest score of 0.89612 is the most suitable educational content according to the quality standards, while the video with the lowest score of 0.158256 has lower quality. With this system, content creators can more efficiently design engaging, informative, and educationally impactful content strategies.